Influencer Marketing, Personal Branding Image, And Affiliate Marketing Against Tiktok Shop Consumer Impulsive Buying - Aisyah Andriani; Misti Hariasih; Rita Ambarwati Sukmono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to identify the influence of Influencer Marketing, Personal Branding, and Affiliate Marketing on Consumer Impulsive Buying at the Tiktok Shop. The population in this research is consumers using Tiktok Shop (aged 11-39 years) in East Java with the sample size determined using the Slovin formula in this quantitative research being 110 respondents, who were selected using probability sampling techniques with random sampling type. In other words, there is an equal opportunity for people to be sampled with the characteristics of the sample used in the research, namely customers who have shopped on the TikTok Shop application and active TikTok Shop users. The data collection technique in this research uses questionnaire data with a linked measurement scale using data processing software tools, namely the Statistics Program for Social Science (SPSS). The results of the research obtained are that Influencer marketing, personal branding, Affiliate marketing influence impulsive buying at the Tiktok Shop. It can be concluded that there is a significant influence simultaneously or together between Influencer Marketing, Personal Branding, and Affiliate Marketing on the Impulsive Buying of Tiktok Shop Consumers.